PENGARUH KINERJA KEUANGAN, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ADVERTISING, PRINTING DAN PERANGKATNYA YANG TERDAFTAR DI BEI TAHUN 2019-2022 DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING - Imaniyah, Della Ulfa; Arief, Mohammad Yahya; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Finance is a sub-field in a company that is related to how to manage funding sources, funding opportunities, investment decisions, and capital structure. The company can decide to determine the capital structure that the company should have through capital structure management. To achieve this goal the company must pay attention to the company's financial management. Advertising, printing and equipment sector companies consisting of 24 companies. The purpose of this research is to test and analyze the influence of financial performance, dividend policy, and company size on company value with share price as an intervening variable. This research uses quantitative research methods. The populations in this research are companies listed on the Indonesia Stock Exchange (BEI) with a sample of 8 companies. This sampling technique uses a non-probability sampling technique with a purposive sampling technique. The data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that financial performance has a negative but not significant effect on stock prices, dividend policy has a negative but not significant effect on stock prices, company size has a significant positive effect on stock prices, financial performance has a negative but not significant effect. The significant effect on company value, dividend policy has a positive but not significant effect on company value, company size has a negative but not significant effect on company value, share prices have a significant positive effect on company value, financial performance has a negative but not significant effect on company value through share prices , dividend policy has a negative but not significant effect on company value through share prices, and company size has a positive but not significant effect on company value through share prices.